Protective Effect Of Vitamin E On Imatinib Induced Histomorphological Changes In Hepatic Central Vein Dilatation In Albino Rats: Light Microscopic Study (Journal of Pharmaceutical Negative Results, 2021)
Background: Imatinib, a potent inhibitor of tyrosine kinases that have been approved for the treatment of chronic myeloid leukemia as well as gastrointestinal stromal tumors, is associated with hepatic toxicity including central vein dilatation and portal hypertension. Vitamin E has antioxidant effects and may have a protective effect against this Histomorphological change in hepatic central vein dilatation.Aim: To observe the possible protective effect of vitamin E against imatinib-induced hepatic central vein dilatation in albino rats.Study Design: A cross-sectional studyPlace and duration of study: Department of Anatomy Peshawar Medical College from 1st Jan 2021 to 31st July 2021.Methodology: One hundred male albino rats of Sprague Dawley strain weighted between 150 -200g were divided into four groups; control, (A) imatinib treated (B), vitamin E treated (C), and combination of both imatinib and vitamin E (D) The drugs were given daily for 4 weeks. Hepatic tissue was fixed overnight in 10% buffered formalin for preservation and processed onto paraffin wax blocks before staining with hematoxylin/eosin as follows: The hepatic central vein caliber was examined under a light microscope using a stage micrometer.Results: The average age of albino rats used in this study was 12 weeks ±2 weeks. Group B rats: In the Imatinib group (group B), 85% of the animals showed marked dilatation in central hepatic veins with a dilation magnitude of 2,500±3002,500±300 micrometers. Results As compared with the control (Group A), central vein changes were accessed in 96.6% of rats on ten protocols treated except the Vitamin E group (Group C, P <0.05). The mean value for dilated diameters was 2,700±1,400 micrometers. Group D tends to have more pronounced hepatocytic necrosis as tested by the percentage of damage area around the central vain than the other four groups (Pooled t =-13.x40, P<0..01)。 In the Combination group (Group D), central vein dilatation was seen in only 20% of rats, which differed significantly from that reported for Imatinib treated animals and had a mean dilation in this group was 1,000±2001,000 ± 2001,000±200 micrometers, (Table III). These results confirm the protective effect of vitamin E on imatinib-induced hepatic central vein dilatation (% showed an 18% decrease), expressing it as rescue rather than increasing or having a double-edged protection role. These differences were statistically significant (all p-values <0.05 using a series of statistical analyses).Conclusion: Imatinib causes hepatic central vein dilatation in albino rats that is reduced by intake of vitamin E. This suggests that antioxidant therapy might ameliorate hepatic toxicity accompanying imatinib treatment in these patients, opening the way for clinical trials to evaluate this therapeutic possibility.